PENGARUH POSITIONING ROYAL CHOCOLATE DONUTS & COFFEE (RO.CHO) TERHADAP PENINGKATAN MINAT BELI KONSUMEN - Syafruddin, Yulianti (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2019)
Positioning is a communication strategy related to how the audience places a product, brand or company in their brains, in their imagination, so that the audience has a certain assessment. This research was conducted in order to determine how the influence of positioning Royal Chocolate Donuts & Coffee (Rho.Cho) on increasing consumer buying interest. This research was conducted using quantitative methods. Data were collected through questionnaires to consumers Rho.Cho Donuts as respondents. The results showed that there was an effect of positioning Ro.Cho donuts on increasing consumer buying interest by 33.9%. The test results show that the variable (X) of product category positioning has a significant influence on the dependent variable of increasing consumer buying interest. While the remaining 66.1% are other variables not examined in this study. Based on the results of these studies, the positioning of Ro.Cho donuts can affect the increase in consumer buying interest.